Comparsion of Outcomes of Single Versus Multiple Mini-Tract Percutaneous Nephrolithotomy for Staghorn Renal Stone Clearance - Tariq Ijaz, Bakhtawar Gul Wazir, Mohammad Asad Shamsher (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Staghorn calculi are branched stones that contain extra than Failure to cast off staghorn calculus might also additionally ruin the parenchyma and kidney feature and motive life-threatening sepsis. Therefore, whole elimination and clearance rates are more often than not taken into consideration while managing staghorn stones. The aim of this study was to investigate the efficacy and safety of multi-tract percutaneous nephrolithotomy (PNL) against the benchmark of the single tract approach. Material and Methods: A randomized clinical trial was conducted at institute of kidney disease Peshawar “between 1stMarch 2022 to 31st Oct 2022” after fulfilling the inclusion criteria. A total 100 patients were included in this study using consecutive non portability sampling technique. Patients who received single- or multiple-tract mPCNL depended on the stone complexity of their computed tomography (CT) images before the operation. In addition, 50 patients who underwent the single mini-tract (<21-Fr sheath) percutaneous method (Group A) compared with 50 patients who required multiple (≥2) mini tracts (Group 2) Results: A total 100 patients with staghorn calculi (Male 33(57.8%) , Female 21(48.8%) and Male 23 (40.3%) , Female 22 (51.1% ) were treated with two types of tracts for mini PCNL, i.e single- and multiple-tract mini PCNL, respectively. The mean stone size was in single tract was 12.67±8.06 and multiple tracts was 17.23±10.49; a significant difference in stone size in Groups A and B, respectively; (P = 0.005). In addition, the Stone Hounsfield unit means score in single tract was 919.73 and multiple tracts were 1070.11. S. T. O. N. E. score in Group 2 was significantly higher (8.4±1.7 10.6±1.3 = 0.001). Practical Implication: In this study a multi-tract PCNL has been shown to be an effective and secure expansion of a single-tract PCNL for big stone burden and complex kidney stone disease. The benefit of this study was to investigate the efficacy and safety of multi-tract percutaneous nephrolithotomy (PNL) against the benchmark of the single tract approach. Conclusion: A multi-tract PCNL has been shown to be an effective and secure expansion of a single-tract PCNL for big stone burden and complex kidney stone disease in this randomised clinical trial single-center investigation. Future prospective studies should concentrate on how well the technique can help individuals with severe stone disease require fewer interventions before becoming stone-free. Keywords: Multiple-Tract, Percutaneous Nephrolithotomy, Staghorn Calculi, Kidney Stone Disease,